Evidences of red panda in Rachuli VDC, Kalikot district, Nepal - Dangol, Bishok; Chalise, Mukesh Kumar (Journal of Natural History Museum, 2018)
Presence of the red panda was assessed in Rachuli Village Development Committee (VDC)(latitude 290 1.98’ N to 2903.57’ N and longitude 81013.52’ E to 81015.87’ E, at altitudinal range between 1800 to 4400 masl), Kalikot, mid-west Nepal. The interaction and interviews with local peoples was organised to collect initial confirmation on occurrence of the red panda. For sign survey of animal, altogether 20 quadrate plots (each of 10×10 sq. meters) at the point where pellets of red panda were found, were laid between altitude of 2800 m to 3300 masl. The presence of Red panda pellets in the study area was major evidence of presence of redpanda in the area. The lowest altitude in which pellet found was 2993 m and the highest was3297 m. The highest number of pellets was observed in altitudinal range of 3100 m to 3150m. The average number of pellets per group was 10.13 ± 5.33. The typical dominant species of trees in red panda habitat were Betula utilis, Abies spectabilis and Quercus semecarpifolia observed with the highest Important Value Index (IVI) of 83.80, 75.83 and 52.80 respectively. Nigalo (Thamnocalamus sp.), the most preferable food plant of red panda, was distributed widely in the study range. The number of pellets groups in the plots and nigalo density were positively correlated (0.795, significant statistically at 0.01 levels (2-tailed)).